Failing Industry 4.0: A Case Study of a SME in the Czech Republic - Marcel Rolf PFEIFER (Communications of International Proceedings, 2021)
Industry 4.0 promises to be the future of competitiveness for companies all around the world. While start-ups focus on this area and big companies try to implement smart principles in production, small and medium-sized enterprises (SME) are waiting for their time to come. This article analyzes how a Czech manufacturing company in the transition from small to medium size understood and mastered the implementation of industry 4.0 principles. Failing to meet its own targets the company decided to abort the project due to lack of financial, technical, and human expert resources. The research monitored the SME over a period of four years. While the targets were set in the initial stage already, the outcome was assessed after the full period. Errors and deviations occurring were mapped and employees were asked for their perception on why the company failed. The lack of experience led to a misinterpretation of the target-setting in the initial phase. While the first targets of the project were not even belonging to industry 4.0 principles, the company decided after their implementation to abort the project, leaving the core projects aside. Overestimating own strengths and expertise and underestimating the challenge made the company management reconsider the whole project. It was concluded that the implementation was neither needed nor doable for the SME. This case study gives an insight on the reality of an SME. While failing to understand the principles and underestimating the challenges, the SME management also failed to stick to the project. Assuming SMEs around the world to have similar issues, these companies require external support and knowledge in order to transit towards industry 4.0 asking for a strategy. In case the culture and mentality cannot be changed, SMEs globally may end in a failed transition.
Keywords: Industry 4.0; Case study; Transition; Failure